2014
DOI: 10.1017/s095834401400007x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of using corpora on revision tasks in L2 writing with coded error feedback

Abstract: This study reports on the results of classroom research investigating the effects of corpus use in the process of revising compositions in English as a foreign language. Our primary aim was to investigate the relationship between the information extracted from corpus data and how that information actually helped in revising different types of errors in the essays. In 'data-driven learning', previous research has often failed to provide rigorous criteria for choosing the words or phrases suitable for correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 27 publications
6
62
1
2
Order By: Relevance
“…A few studies have investigated text-based feedback with additional affordances such as the use of Markin (a Windows-based tool that allows for inserting of color-coded premade feedback codes in a short text) in Byrne's (2007), hyperlinked explanations as in Yeh and Lo's (2009) "Online Annotator for EFL Writing" or Gaskell and Cobb's (2004) premade hyperlinks to relevant concordance lines and tools bridging the feedback with corpus study and language tools. Others have employed basic features of electronic text feedback such as underlining and error coding for novel uses such as to prompt corpus use (Tono, Satake, & Miura, 2014). Further investigation into the incorporation of additional affordances may bring to light valuable resources for providing meaningful feedback to students on their writing.…”
Section: Text-based Electronic Feedbackmentioning
confidence: 99%
“…A few studies have investigated text-based feedback with additional affordances such as the use of Markin (a Windows-based tool that allows for inserting of color-coded premade feedback codes in a short text) in Byrne's (2007), hyperlinked explanations as in Yeh and Lo's (2009) "Online Annotator for EFL Writing" or Gaskell and Cobb's (2004) premade hyperlinks to relevant concordance lines and tools bridging the feedback with corpus study and language tools. Others have employed basic features of electronic text feedback such as underlining and error coding for novel uses such as to prompt corpus use (Tono, Satake, & Miura, 2014). Further investigation into the incorporation of additional affordances may bring to light valuable resources for providing meaningful feedback to students on their writing.…”
Section: Text-based Electronic Feedbackmentioning
confidence: 99%
“…In several studies, the general corpora were not provided directly to students but offered through an online link. Tono et al [22] introduced a publicly available online corpus query system IntelliText in which the students could consult ready-made corpora including the BNC. Compared with the direct use of BNC, IntelliText provided a more user-friendly interface where students were limited to search merely word or phrase levels.…”
Section: Corpora and Corpus Tools Used In These Studiesmentioning
confidence: 99%
“…These studies were mainly conducted by comparing the usefulness of different reference tools; however, Geluso [32] made a different comparison, which contrasted learners' initial Google-informed phrases vs final nonGoogle-informed phrases, suggesting that Google could be an effective reference tool to improve the naturalness of their productive language use. Unlike the above two streams of studies, Tono, et al [22] concerned about the effectiveness of DDL in correcting different types of errors in writing. In this study, students were required to consult corpora for correcting three types of lexico-grammatical errors in writing.…”
Section: Research Focus and Major Findingsmentioning
confidence: 99%
“…The benefits of the use of corpora and Data Driven Learning (DDL) have been well documented over the last two decades [21,24,33]. Through meta-analyses of DDL studies, it has been shown that DDL can be effective for learning EFL grammar and vocabulary [18,27].…”
Section: Ddl In the Efl Classroommentioning
confidence: 99%